2010
DOI: 10.3724/sp.j.1141.2010.02131
|View full text |Cite
|
Sign up to set email alerts
|

A New Problem with Cross-Species Amplification of Microsatellites: Generation of Non-Homologous Products

Abstract: Abstract:Microsatellites have been widely used in studies on population genetics, ecology and evolutionary biology. However, microsatellites are not always available for the species to be studied and their isolation could be time-consuming. In order to save time and effort researchers often rely on cross-species amplification. We revealed a new problem of microsatellite cross-species amplification in addition to size homoplasy by analyzing the sequences of electromorphs from seven catfish species belonging to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…The use of microsatellite marker in population genetic studies is still a subject of controversy since size homoplasy, i.e., the fact that an allelic class could include alleles identical by descent (truly homologous) as well as alleles that achieved the same length via convergent evolutionary events (Orti et al, 1997), is a limit intrinsic to the microsatellite-based approach (Taylor et al, 1999), mainly due to the fact that mechanisms of mutation in microsatellites are incompletely known (Yue et al, 2010). However some authors reported that the extensive variability at microsatellite loci combined with the increase in the number of microsatellite markers studied often compensated for their homoplasious evolution (Estoup et al, 2002;Koskinen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The use of microsatellite marker in population genetic studies is still a subject of controversy since size homoplasy, i.e., the fact that an allelic class could include alleles identical by descent (truly homologous) as well as alleles that achieved the same length via convergent evolutionary events (Orti et al, 1997), is a limit intrinsic to the microsatellite-based approach (Taylor et al, 1999), mainly due to the fact that mechanisms of mutation in microsatellites are incompletely known (Yue et al, 2010). However some authors reported that the extensive variability at microsatellite loci combined with the increase in the number of microsatellite markers studied often compensated for their homoplasious evolution (Estoup et al, 2002;Koskinen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…elegans . Nevertheless cross-amplification from congeneric species is not generally feasible because inherent problems like allele size homoplasy, polymorphisms biases, null alleles presence, broken repeats motifs or amplification of non-orthologous loci could arise 15 18 . Thus, de novo development of species-specific microsatellite markers is strongly recommended.…”
Section: Introductionmentioning
confidence: 99%
“…No such markers have been developed to date for congeners of I. longirostris limiting our ability to resolve fine-scale differentiation and subdivision patterns among populations. Moreover, cross-amplification of microsatellite loci developed from other species often presents problems such as allele size homoplasy, unsuccessful amplification in phylogenetically distant species, lower levels of polymorphism, null alleles, broken repeat motifs and amplification of non-orthologous loci (Primmer et al, 2005; Barbará et al, 2007; Rutkowski, Sielezniew & Szostak, 2009; Yue, Balazs & Laszlo, 2010). …”
Section: Introductionmentioning
confidence: 99%